Developing Economically Viable Antenna Systems to Ensure Dependable Long-Range Communication in Rural Areas of Iraq - Haroon Rashid Hammood Al Dallal (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
The objective of this project is to develop cost-effective antenna systems. The study utilized AutoCAD 2006 for data analysis and visualization. This article provides a detailed examination of various antenna systems, including cable/wire, log-periodic, array, helical, and aperture antennas. The research also explores several parameters related to antenna systems, such as effective length, antenna gain and directivity, active aperture, bandwidth, polarization, input impedance, power gain, radiation efficiency, radiation pattern, and radiation intensity. The main goal is to identify the challenges in designing cost-effective antenna systems for reliable communication. These challenges include design issues, contract management difficulties, fluctuating material prices, inaccurate estimations, limited wireless communication technology, and financial constraints. The study examines a wavelength range from 16.7 to 120, corresponding to distances from 10,000 km to 120,000 km. The findings show that at a frequency of 600 MHz, a wavelength of 16.7 units covered a distance of 10,000 km. Similarly, at 750 MHz, a wavelength of 53.3 units covered 40,000 km, and at 850 MHz, a wavelength of 94.1 units spanned 80 km. At 1000 MHz, a wavelength of 120 units covered 120,000 km. This study offers valuable insights into the design of cost-effective antenna systems and provides an understanding of the factors that influence their performance in practical communication scenarios.